Standards for Assay of von Willebrand Factor Concentrates: A Collaborative Study - Fricke, W A; Lamb, M A; Rastogi, S C (Thrombosis and Haemostasis, 1993)
A multilaboratory collaborative study was undertaken to assess the feasibility of using a plasma standard for expressing the results of assays for the von Willebrand factor content of von Willebrand factor concentrates and of factor VIII concentrates. Thirteen laboratories tested six concentrates for von Willebrand factor antigen, ristocetin cofactor activity, and multimer content using the World Health Organization plasma standard for factor VIII/von Willebrand factor, 87/718, as a standard. Only a few assays were invalid because of nonparallelism or nonlinearity. Significant interlaboratory and interassay differences were found for both von Willebrand factor antigen and ristocetin cofactor activity. There was generally good agreement between the laboratories with respect to the multimer content in the preparations. With respect to assay validity, a plasma standard could be suitable for assaying concentrated preparations of von Willebrand factor.